Exploring diversity in sustainability assurance practice: Evidence from assurance providers in the UK. Issue 2 (20th March 2019) - Channuntapipat, Charika; Samsonova-Taddei, Anna; Turley, Stuart
Abstract : Purpose: The purpose of this paper is to understand sustainability assurance (SA), and diversity in that practice, by examining assurance providers' understandings of the practice and the influences that those understandings have on the actual assurance process. It focuses on the issues beyond the content of statements in SA reports. Design/methodology/approach: This paper employs semi-structured interviews, supplemented by textual data sources. Research participants are assurance providers in the UK, including those within and outside the accounting profession. Drawing on the perspective of actor-network theory, the study focuses on the associations between different actors and how those shape the assurance practice. Findings: The findings indicate that providers' understandings of SA practice vary significantly. This variation has a major effect on how the assurance practice is conducted. The study identifies four types of SA engagements, which are designated as: social assurance, integrated assurance, formative assurance and compliance assurance. Such a categorization provides a broad-based understanding of the operationalization of SA and the degree of heterogeneity within it. Originality/value: This paper extends the understanding of SA by focusing on the practice beyond the statements made by assurance providers, which have been the predominant focus of analysis in the existing literature, and by offering a categorization of the diversity in practice. The focus on the associations between assurance providers and other actors provides a new perspective for exploring the fundamentals of the practice.